Impacts of moving wall and heat-generating element on heat transfer and entropy generation of A2O3/H2O nanofluid - Bondarenko, Darya S.; Sheremet, Mikhail A.; Öztop, Hakan Fehmi; Ali, Mohamed E. (Springer, 2019)
Development of various electronic devices demands to create effective cooling complexes. The present paper deals with computational analysis of mixed convection cooling of heat-conducting and heat-generating element located inside an alumina-water nanofluid enclosure with upper moving wall. Usage of upper moving wall, nanofluid and cooling vertical walls allows to create the effective cooling process. Analysis has been performed numerically using the Oberbeck- Boussinesq equations. The effects of nanoparticles concentration, heat source location and upper wall velocity on flow structures, heat exchange and entropy generation have been investigated. It has been ascertained that effective cooling of the heated element occurs for high Reynolds number and central position of the heat-generating element.
Keywords: Mixed convection; Entropy generation; Nanofluid; Heat-generating source; Lid-driven cavity; Finite difference method